2002
DOI: 10.1097/00054725-200205000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Role of Infections in the Manifestation or Reactivation of Inflammatory Bowel Diseases

Abstract: The etiology of inflammatory bowel disease (IBD) is unknown. In addition to genetic and environmental factors, microorganisms have been discussed as possibly playing an important role. Recent reports in the literature do not suggest that a specific persistent infection causes IBD, but indicate that enteric pathogens could cause initial onset of IBD and are associated with reactivation of quiescent disease. Despite their self-limited character, these infections initiate a cascade of inflammatory events leading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
8

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 23 publications
1
25
0
8
Order By: Relevance
“…In other words, it should be verified whether specific Ags or PAMPs from the commensal bacteria are essential for the priming or memory phase. Consistently, the current study also provides an explanation of why a common recurrence of IBD is observed during complication of microbial infection, such as acute Salmonella enterocolitis, which may possibly supply large amounts of "bystander" PAMPs (31).…”
Section: Discussionsupporting
confidence: 81%
“…In other words, it should be verified whether specific Ags or PAMPs from the commensal bacteria are essential for the priming or memory phase. Consistently, the current study also provides an explanation of why a common recurrence of IBD is observed during complication of microbial infection, such as acute Salmonella enterocolitis, which may possibly supply large amounts of "bystander" PAMPs (31).…”
Section: Discussionsupporting
confidence: 81%
“…As intestinal infections by enteropathogens are associated with both IBD onset and IBD relapses, stool microbiologic studies are usually advised in patients with IBD relapses [11]. However, the incidence and clinical relevance of such infections have not been appropriately assessed, and only 2 prospective studies including a small number of patients have been published to date.…”
Section: Discussionmentioning
confidence: 99%
“…The tolerance which exists under a normal healthy state towards resident intestinal flora is broken in active IBD [19], which implies the triggering role of bacterial infection in the flare of IBD. As many human infectious pathogens appear in a regular seasonal pattern [20,21], seasonal exposure to infectious agents may induce bursts of immune diseases, such as IBD [22,23], and there may be an association between the month of birth and risk of developing IBD later in life [24]. In the Asian area, bacterial infections show a seasonal pattern of occurrence that peaks in the spring and summer [25,26], but viral infections generally occur in the autumn and spring [27], which is slightly different from the seasonality found in Western populations according to a number of epidemiological studies [28,29].…”
Section: Discussionmentioning
confidence: 99%